(untitled) (Journal of Engineering and Health Sciences, 2023)
This paper is part of an on-going research on the development of maintenance cost and down time model for Higher Education Institution Hostel facility maintenance in Malaysia where the case study is conducted at Universiti Melaka (UNIMEL). The model is developed to analyse the total cost and downtime curve for various values of the uncertain parameter and noting the effect of this variation on the optimal solution. The decision areas addressed based on the replacement action that are assumed to be known with certainty. This is due to the item not being subject to failure but considering the operating cost and downtime with use. The study is aimed to assist Development Maintenance Unit deciding an appropriate replacement policy. This is usually useful to plot the total cost of downtime per unit time curve. The advantage of the curve is that, along with giving the optimal value, it shows the total cost around the optimum. If the curve is fairly flat around the optimum, it is not really very important that engineers should plan for the replacements exactly at the optimum. The model is proposed to guide and facilitate when dealing with optimization problems. If there is uncertainty about the value of the particular parameter required during the analysis, then the replacement cost downtime is uncertain. Furthermore, the evaluation of the total cost and downtime curve for various values of the uncertain parameter could in consequence affect the optimal solution and show the graph in 3 Dimensional (3 D). from this study will get the optimum between cost and downtime model for Hostel Facility Maintenance techniques at Unimel